2019
DOI: 10.1093/brain/awz026
|View full text |Cite
|
Sign up to set email alerts
|

Functional connectivity associated with tau levels in ageing, Alzheimer’s, and small vessel disease

Abstract: In Alzheimer’s disease, tau pathology spreads hierarchically from the inferior temporal lobe throughout the cortex, ensuing cognitive decline and dementia. Similarly, circumscribed patterns of pathological tau have been observed in normal ageing and small vessel disease, suggesting a spatially ordered distribution of tau pathology across normal ageing and different diseases. In vitro findings suggest that pathological tau may spread ‘prion-like’ across neuronal connections in an activity-dependent manner. Supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
181
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 185 publications
(203 citation statements)
references
References 72 publications
22
181
0
Order By: Relevance
“…We observed phospho-tau spreading from 3 to 10 months in 3xTg AD model mice and found that this was associated with long-range connectivity deficits in young model animals. This supports the notion of a tight coupling between functional connectivity and tau progression 35 , supported by molecular work by others 43 . The seeding hypothesis can be further connected to other models of axonal degeneration and inflammatory response 44 and, thus, provides a coherent description of the pathophysiology process taking place in AD.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…We observed phospho-tau spreading from 3 to 10 months in 3xTg AD model mice and found that this was associated with long-range connectivity deficits in young model animals. This supports the notion of a tight coupling between functional connectivity and tau progression 35 , supported by molecular work by others 43 . The seeding hypothesis can be further connected to other models of axonal degeneration and inflammatory response 44 and, thus, provides a coherent description of the pathophysiology process taking place in AD.…”
Section: Discussionsupporting
confidence: 82%
“…Moreover, regions highlighted in the pair-wise correlation analysis were also found to be enriched in tau aggregates within the AD-like disease progression (amygdala and hippocampus, Supplementary Fig. 2), consistent with tau dispersions across functionally connected networks 35 .…”
Section: Local Functional Connectivity Deficits Translate Into Whole-supporting
confidence: 64%
See 1 more Smart Citation
“…Our datadriven approach detected 10 independent spatial patterns of tau across temporal (medial temporal, parahippocampal, lateral temporo-parietal), occipital (left and right inferior occipital), frontal (orbitofrontal, middle frontal, anterior frontal), parietal, and sensorimotor regions. This finding might seem surprising, as several studies have shown that tau is either absent or restricted to temporal regions in cognitively normal individuals [39][40][41]. Our study shows that an unsupervised network approach may reveal additional patterns in tau PET data, which can be used to understand why some individuals, despite being clinically normal, are more prone to accumulate tau in specific brain areas.…”
Section: Discussionmentioning
confidence: 68%
“…Studies decomposing the spatial distribution of tau-PET signal in the human brain have revealed spatial patterns highly reminiscent of brain functional networks [30, 31]. In addition, brain regions with greater functional connections to the rest of the brain tend to have greater tau accumulation [32], and correlations have been found between functional connectivity patterns and tau covariance patterns [33, 34].…”
Section: Introductionmentioning
confidence: 99%